INVESTMENT DECISIONS OF INTERNATIONAL CORPORATIONS IN THE CONDITIONS OF GLOBAL CHALLENGES - PETKOVA, Lesia; LESHCHENKO, Maryna; SAKHNO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides the impact of global challenges on the international corporation’s investment priorities. The COVID-19 pandemic and the war on the European continent force investors to respond quickly to changes in the external environment. The article analyzes the growth rates of the main macroeconomic indicators of the world economy and examines the features of the geographical and sectoral distribution of foreign investment. The instability of the economic environment affects the change in the geographical and sectoral structure of foreign investment. Modern corporations prefer markets with a stable financial situation, a favorable investment climate, and high growth potential. Destructive factors of the international economic environment that influenced the implementation of investment decisions of global corporations in 2020-2023 did not significantly affect the rating of the largest donors and recipients of FDI. The authors highlight a trend towards increasing investment activity in industry, despite the significant predominance of the value and number of investment transactions in the services sector. Industry priorities for investment decisions are shifting towards developing new products and services that contain an innovative component to better meet changing consumer needs. The article identifies key investor expectations as a result of the war in Ukraine for expanding the geography and scale of international business. Responding to global challenges, companies are transforming their business models focused on modern technological solutions and new tools for countering risks. More than half of the jurisdictions note that corporations will rethink their growth and expansion plans, and therefore will have to develop and implement new tools to stimulate investment activity and restore economic growth.
Keywords: foreign investments; international corporations; global challenges; international business; investment activity